Amiloride: A review - Sun, Qianhui; Sever, Peter (Journal of the renin-angiotensin-aldosterone system, 2020)
Amiloride is a potassium retaining diuretic and natriuretic which acts by reversibly blocking luminal epithelial sodium channels (ENaCs) in the late distal tubule and collecting duct. Amiloride is indicated in oedematous states, and for potassium conservation adjunctive to thiazide or loop diuretics for hypertension, congestive heart failure and hepatic cirrhosis with ascites. Historical studies on its use in hypertension were poorly controlled and there is insufficient data on dose-response. It is clearly highly effective in combination with thiazide diuretics where it counteracts the adverse metabolic effects of the thiazides and its use in the Medical Research Council Trial of Older Hypertensive Patients, demonstrated convincing outcome benefits on stroke and coronary events. Recently it has been shown to be as effective as spironolactone in resistant hypertension but there is a real need to establish its potential role in the much larger number of patients with mild to moderate hypertension in whom there is a paucity of information with amiloride particularly across an extended dose range.